INTEGRATING AI WITH AEM: ENHANCING CONTENT CREATION AND DELIVERY - Bhanu Phanindra Babu Gogula, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This article explores the transformative potential of integrating Artificial Intelligence (AI) with Adobe Experience Manager (AEM) for content management and delivery. It examines how AI enhances AEM's capabilities in content automation, personalization, analytics, and cross-channel orchestration. The article presents key statistics on the growing content management market and rising customer expectations. It discusses Adobe Sensei's role in powering AI features within AEM, including intelligent tagging, smart cropping, and personalized recommendations. The article analyzes how AI enables advanced analytics, real-time insights, and content performance optimization. Finally, it explores predictive content delivery and cross-channel content orchestration, highlighting the significant improvements in customer engagement, conversion rates, and business outcomes achieved through AI-AEM integration